RETRACTED: Pengembangan Model Simboling Kelompok Expressive Writing berlandaskan Falsafah Dandang Tingang untuk Meningkatkan Perilaku Respect - Karyanti Karyanti; Muhammad Andi Setiawan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This article has been retracted as a result of multiple publications from the article by the relevant author. Similar articles can be found at the URL https://journal.stkip-andi-matappa.ac.id/index.php/jurkam/article/view/204 or https://dx.doi.org/10.31100/jurkam.v3i1.204